La iglesia ecuatoriana entre el Concilio Vaticano II y la Conferencia de Medellín (Estudios) - Chamorro Espinosa, David (2022)
The Second Ecumenical Council of the Vatican led to social and religious transformations that impacted the lives and beliefs of hundreds of millions of Catholics. The present article addresses how they were implemented in Ecuador. Certain Council documents and issues are mentioned, such as the Church’s reference to poverty, which Monsignor Leonidas Proaño pledged to support. It then provides a description of the pastoral challenges of Pablo Muñoz Vega with respect to the Archdiocese of Quito and the profound transformations in the Diocese of Riobamba. The study concludes in 1968, the year of unrest and the Second Episcopal Conference of Latin America in Medellín, Colombia.